2021
DOI: 10.1109/jeds.2020.3041842
|View full text |Cite
|
Sign up to set email alerts
|

Novel Si/SiC Heterojunction Lateral Double-Diffused Metal Oxide Semiconductor With SIPOS Field Plate by Simulation Study

Abstract: A novel Si/SiC heterojunction Lateral Doublediffused Metal Oxide Semiconductor with the Semi-Insulating Polycrystalline Silicon field plate (SIPOS Si/SiC LDMOS) is proposed in this paper for the first time. The innovative terminal technology of Breakdown Point Transfer (BPT) had been applied on Si/SiC MOSFETs. This creative technology improved Breakdown Voltage (BV) of the proposed device, compared with the conventional Si LDMOS (Cov. LDMOS). In order to optimize the trade-off between BV and Specific On-Resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Detailed electrothermal modelling techniques for power semiconductor devices can be categorized into five types based on literature: (a) behavioural model [26], [46], [47], (b) physical model [48], [49], (c) semi-physical model (i.e., PSpice or SaberRD/ SaberEXP) [50]- [52], (d) numerical model (i.e., numerical tools such as ISE TCAD and MEDICI) [53], [54] and (e) semi-numerical model [55]. The physical models are represented by the composition of the internal layers of the semiconductors [48], [49].…”
Section: F Detailed Electro-thermal Modelling and Validation Of The Ibc At Full Load Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed electrothermal modelling techniques for power semiconductor devices can be categorized into five types based on literature: (a) behavioural model [26], [46], [47], (b) physical model [48], [49], (c) semi-physical model (i.e., PSpice or SaberRD/ SaberEXP) [50]- [52], (d) numerical model (i.e., numerical tools such as ISE TCAD and MEDICI) [53], [54] and (e) semi-numerical model [55]. The physical models are represented by the composition of the internal layers of the semiconductors [48], [49].…”
Section: F Detailed Electro-thermal Modelling and Validation Of The Ibc At Full Load Conditionmentioning
confidence: 99%
“…Hence, the simulation speed is slow because the switching behavior needs to be simulated in detail. The numerical models in [53], [54] also have a high computation time due to the required settings of material performance and the geometry size of the devices. Furthermore, the semi-numerical models in [55] are based on geometrical microstructure parameters and composite elastic properties that are obtained using finite element analysis (FEA); hence, this type of model is not a potential candidate for .…”
Section: F Detailed Electro-thermal Modelling and Validation Of The Ibc At Full Load Conditionmentioning
confidence: 99%
“…Some researchers embed heterojunction diodes in power devices to improve the electrical performance of the devices. [24][25][26][27][28][29] Yu et al [24] reported a novel SiC power MOS-FET structure. Yoon [25] proposed a SiC MOSFET insted heterojunction diode, which provided some protection against the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Silvaco T-CAD Atlas software 5.34.0.R [8][9][10][11] was used to perform n-LDMOS modulation simulations. The plate effect [12][13][14][15][16][17] was employed to arrange a floating poly [17][18][19] on the oxide layer (STI). The design was intended to take advantage of the field-saka effect to increase the breakdown voltage (VBK) while reducing the maximum electric field.…”
Section: Introductionmentioning
confidence: 99%